SENTIMEN ANTI BARAT ULAMA TIGA SERANGKAI DALAM TAFSIR AL-QUR’ANUL KARIM - Maharani Wulandari; Khusnul Khotim (CV. Adiba Aisha Amira, 2023)
Tafsir Al-Qur'anul Karim is the earliest tafsir book in the 19th century in the Malay region and has had a great impact. It was written by a triad of scholars consisting of Abdul Halim Hasanm Zainal Arifin and Abdurrahman. The writing of the tafsir book against the backdrop of Dutch colonization has given nuances of anti-Western sentiment in its interpretation. To prove this claim, the researcher will trace the interpretations in the tafsir book that cornered Western civilization and their religion. This research method is descriptive analytical. The results of this study show that the ulama of the triad always expose the ugliness of western culture to show that Islam is superior. But at the same time, they ignore and do not criticize similar vices that